Anti-TNF biosimilars in Crohn's Disease: a patient-centric interdisciplinary approach. (3rd August 2019) - Peyrin-Biroulet, Laurent; Danese, Silvio; Cummings, Fraser; Atreya, Raja; Greveson, Kay; Pieper, Burkhard; Kang, Taegyun
ABSTRACT: Introduction : The purpose of this review is to highlight the role of biosimilars in early treatment in IBD and introduce ways to facilitate a patient-centric switching process through multidisciplinary approach. Areas covered : We summarize existing scientific literature related to the role of biosimilars in inflammatory bowel disease in terms of early treatment and cost-saving and implementing switching process. Expert opinion : Use of anti-TNF biosimilars in patients has the potential for large drug-acquisition cost-saving, which can be reinvested into early treatment. Managed switched programs for adalimumab can add further benefits in the future.